Monetary compensation for unfair dismissal: a comparative study in the United Kingdom and Malaysia - Abdul Shukor, Siti Fazilah; Ali Mohamed, Ashgar Ali; Ab Hamid, Zuraini (IIUM Press, International Islamic University Malaysia, 2019)
Although unfair dismissal is not considered as a new issue in the current era, it may nevertheless severely affect the employees' right to earn a salary and other benefits such as retirement saving, among others. In order to recompense the employee's rights of employment, the legislature in many jurisdictions has introduced reinstatement as the remedy for unfair dismissal. Unfortunately, reinstatement is not awarded in most cases due to the long delay from the date of dismissal to the date of an award which may take a few years, where in the meantime the claimant may have comfortably settled in his new employment and in most cases would not desire reinstatement. Realising the above, the legislature has allowed the alternative remedy of monetary compensation for unfair dismissal. In fact, today, monetary compensation has becomethe remedy in both Malaysia and the United Kingdom. The Employment Rights Act 1996 of the United Kingdom recognises several remedies for unfair dismissal such as reinstatement, re-engagement, and monetary compensation. On the other hand, the Malaysian Industrial Relations Act 1967 merely provides reinstatement as the remedy for unfair dismissal; however, monetary compensation has been allowed vide the Industrial Court Practice Direction No. 1 of 1987, to be awarded at the discretion of the Industrial CourtChairman. In light of the above, this article discusses the awardingof monetary compensation in the United Kingdom and Malaysia with reference to legislation and decided cases in the above jurisdictions.